Identification test of bacterial species and resistance genes from infectious patients using MDR direct flow chip molecular technique compared to conventional techniques - Surjawinata, Mario; Sudarmono, Pratiwi; Lestari, Resti Hardianti (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Introduction: Antimicrobial resistance poses a threat to global public health by increasing morbidity and mortality. While resistance development is a natural biological process, antibiotic use has accelerated its rise resistance. This study aimed to determine the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the MDR Direct Flow Chip Kit to detect 5 bacterial species and a total of 55 resistance gene markers. Methods: The research employed a cross-sectional design, analyzing positive samples determined by the VITEK® 2 system from various specimens, including sputum, pus, and blood. These specimens were collected from sepsis patients at the FKUI Clinical Microbiology Laboratory in 2023. They were stored in Eppendorf tubes with TSB and Glycerol fluids, then cultured on Nutrient Agar Media and incubated overnight. HybriSpot® will analyze the increasing isolates using the MDR Direct Flow Chip, an in vitro diagnostic kit that quickly detects multidrug-resistant bacteria. This kit employs multiplex PCR to identify five bacterial species—Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, and Acinetobacter baumannii—as well as 55 resistance gene markers. These markers include the primary enzymatic mechanisms associated with nine different antibiotic classes. Result: A total of 40 samples were analyzed with HybriSpot® using the MDR Direct Flow Chip, which identified 5 genus species and detected 31 resistance genes. The same samples were also tested with the VITEK® 2 system, which identified the same 5 genus species and provided antibiotic susceptibility results. The overall sensitivity was 80%, specificity was 94.2%, and conformity was 94.68%. Conclusion: The MDR Direct Flow Chip assay is a promising method for identifying pathogens in positive blood cultures of infected patients and can aid antimicrobial stewardship programs in hospitals.